Pengaruh Dosis Pupuk NPK Mutiara dan Konsentrasi Larutan Daun Sirzak terhadap Hasil Tanaman Jeruk Siam (Citrus nobilis Var. Microcarpa L.). - I Gede Ariandika; Ni Komang Alit Astiari; Ni Putu Anom Sulistiawati (Fakultas Pertanian, Universitas Warmadewa, 2021)
This study aims to determine the effect of the dose of pearl NPK fertilizer and the concentration of soursop leaf solution on the yield of Siamese orange (Citrus Nobilis Var. Microcarpa L.) and their interactions, which were carried out in Belancan Village, Kintamani District, Bangli Regency from December to July 2021. This study used a randomized block design (RAK) with 2 factors arranged in a factorial manner. The first factor tested was the dose of pearl NPK fertilizer (M) which consisted of 4 levels, namely: M0 (0 g/tree), M1 (150 g/tree), M2 (300 g/tree) and M3 (450 g/tree). While the second factor is the concentration of Sirzak leaf solution (D) which consists of 3 levels, namely: D0 (0 ml/l water/tree), D1 (40 ml//l water/tree) and D2 (80 ml/l water/tree). Thus, there were 12 combination treatments, each of which was repeated 3 times so that 36 citrus trees were needed. The results showed that the interaction between the dose of pearl NPK fertilizer and the concentration of sizak leaf solution had no significant effect on all observed variables. The highest harvested fruit weight per tree was obtained at a dose of NPK Mutiara 450 g/tree, which was 8.54 kg, an increase of 52.77% when compared to that without pearl NPK fertilizer (control), which was only 5.59 kg. While the concentration treatment of soursop leaf solution obtained the highest harvested fruit weight per tree was obtained at a concentration of 80 ml/l/tree which was 8.54 kg, an increase of 40.93% when compared to without soursop leaf solution, which was only 6.06 kg.